A closer look at the locked-wheel pavement friction data in the ltpp database for selected states. Issue 1 (1st January 2019) - Murad, Maher M.; Abaza, Khaled A.
Abstract: Pavement friction data from the Long-Term Pavement Performance (LTPP) database were treated and analyzed in order to examine its quality, patterns, and potential use. Data from a number of states along with Puerto Rico, Ontario, and Saskatchewan were sorted by availability of traffic information, testing temperature, and pavement type. The majority of the sections considered have relatively low ESAL. There is evidence of good quality control in Friction Number (FN) measurements. The difference in FN values between the beginning and end of a section is consistent with ASTM standards. The distribution of FN measurements can be used as a pavement management tool to identify sections that may need maintenance for friction restoration. There is a great deal of variability in the FN data in spite of temperature correction, especially at higher values of ESAL. Many of the selected sections display a trend of general decrease in FN at higher ESAL. However, factors other than traffic, such as mix design properties, may also need to be considered. Some testing information, such as the tire type used, is not available in the database and was obtained by an external survey. Traffic data in the form of Equivalent Single Axle Load (ESAL) are available, but not for the entire life of the pavement, and had to be supplemented with projections. The friction data in the LTPP database can be more useful for researchers and professionals if updated to include some missing parameters.